2019
DOI: 10.1111/1365-2435.13403
|View full text |Cite
|
Sign up to set email alerts
|

Can hot temperatures limit disease transmission? A test of mechanisms in a zooplankton–fungus system

Abstract: Thermal ecology theory predicts that transmission of infectious diseases should respond unimodally to temperature, that is be maximized at intermediate temperatures and constrained at extreme low and high temperatures. However, empirical evidence linking hot temperatures to decreased transmission in nature remains limited. We tested the hypothesis that hot temperatures constrain transmission in a zooplankton–fungus (Daphnia dentifera–Metschnikowia bicuspidata) disease system where autumnal epidemics typically … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…The infection rates were inhibited in summer, while they increased after the weather turned cool (Cáceres et al, 2006). Nevertheless, Shocket et al (2019) found that although high temperatures decreased the yield of spores and harmed the free living spores of M. bicuspidata, this effect did not fully explain the lack of summer epidemics in a Daphnia zooplankton host. Dallas and Drake (2016) found that temperature fluctuations can reduce the spread of M. bicuspidata.…”
mentioning
confidence: 93%
“…The infection rates were inhibited in summer, while they increased after the weather turned cool (Cáceres et al, 2006). Nevertheless, Shocket et al (2019) found that although high temperatures decreased the yield of spores and harmed the free living spores of M. bicuspidata, this effect did not fully explain the lack of summer epidemics in a Daphnia zooplankton host. Dallas and Drake (2016) found that temperature fluctuations can reduce the spread of M. bicuspidata.…”
mentioning
confidence: 93%
“…A recent study on a freshwater invertebrate–pathogen system measured different components of disease transmission at several temperatures and found that the most important impacts were on the fungus itself. They demonstrated that the spores of the fungus Metschnikowia bicuspidata were most infectious when produced in the zooplankton hosts at an intermediate temperature and declined in infectiousness when exposed to increasing temperatures as free‐living spores (Shocket et al, 2019). We did not test either of these scenarios, but as far as we are aware, there is no evidence of temperature sensitivity in baculoviruses.…”
Section: Discussionmentioning
confidence: 99%
“…While examples of temperature‐induced changes in disease prevalence in natural populations have already been identified, the mechanisms are poorly understood. Few empirical studies address how different components of disease transmission respond to thermal change (but see Shocket et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…shown to be more infectious to their subsequent host (Altman et al, 2016;Shocket, Vergara, et al, 2018), although hot temperatures prior to contacting a host can lead to a decrease in infectiousness (Shocket et al, 2019). How prior thermal experience affects host thermal limits during infection will therefore depend on the interaction between both host and pathogen thermal plasticity; something which models of disease dynamics parameterized from constant temperature experiments will not be able to account for (see also Raffel et al, 2013).…”
Section: Not All Ind Ividual S Within a P Opul Ati On Will Suffer A Reduc Ti On In Thermal Limits Equallymentioning
confidence: 99%